2022
DOI: 10.25236/ajhss.2022.051603
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of the Russia-Ukraine War on U.S. Stock Market: Event Study Analysis and Fuzzy Set Approach

Abstract: Although many studies take the event study and fuzzy set approach, there is a lack of studies on the impact of international conflict on different sectors within a country. This study uses this approach to calculate abnormal return and cumulative abnormal return to investigate the impact of the Russia-Ukraine war on the U.S. Stock Market of 20 representative companies of 10 U.S. sectors. Covering a 10-day timeframe before and 10-day window following the start of the war which was on 24 February, 2022, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Similarly, investor sentiment during the Russian invasion was found negative due to increased volatility (Najaf, Joshipura, and Alshater 2023). Whereas Richad, Astawa, and Tonggok (2023) found mixed reactions of investor sentiment, with increasing energy sectors' stock and decline in consumer goods stocks; negative impact on airlines stocks, herding behavior in energy markets but, benefiting the market for military goods (Ahmed, Hasan, and Kamal 2022); adverse effects on some industries like finance, while other remained unaffected (Lai et al 2022); stability of overall stock returns (Izzeldin et al 2023). Yousaf et al (2023) showed an increased volatility connectedness, particularly short‐term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, investor sentiment during the Russian invasion was found negative due to increased volatility (Najaf, Joshipura, and Alshater 2023). Whereas Richad, Astawa, and Tonggok (2023) found mixed reactions of investor sentiment, with increasing energy sectors' stock and decline in consumer goods stocks; negative impact on airlines stocks, herding behavior in energy markets but, benefiting the market for military goods (Ahmed, Hasan, and Kamal 2022); adverse effects on some industries like finance, while other remained unaffected (Lai et al 2022); stability of overall stock returns (Izzeldin et al 2023). Yousaf et al (2023) showed an increased volatility connectedness, particularly short‐term.…”
Section: Literature Reviewmentioning
confidence: 99%